Ten years on: what can Google Earth offer the geoscience community?. (November 2015) - Mather, A.E.; Mills, S.; Stokes, M.; Fyfe, R.
Abstract : Google Earth has been part of most geoscientists' computer (and mobile) desktops for a decade, and this year Google Earth Professional has become freely available to all with a universal license key. Many users are still, however, not aware of the full potential that it can offer across a range of teaching and research areas in the geosciences. Here a pragmatic look is taken at some of the current key uses in terms of resources and applications and how they can help in research and training educational roles in the geosciences.